The Application of Digital Payments (QRIS & E-Wallet) on the Efficiency of MSME Transactions - Zakariya, Achmad; Arifin, Ah. Ali (Laboratorium Riset Ekonomi, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia are becoming more competitive and efficient because to the digital transformation of payment systems. Through a literature review of numerous national and international studies carried out between 2020 and 2025, this study seeks to analyze the effects of the implementation of the Indonesian Standard Quick Response Code (QRIS) and e-wallets on transaction efficiency, financial recording, customer loyalty, and MSME access to financing. The study's findings demonstrate that the use of digital payments can decrease cash error rates through automated recording, expedite transaction times, and save operating expenses. Additionally, the digital footprint of transactions boosts MSMEs' financial reputation, increasing their chances of obtaining official financing. E-wallets are strategically important in marketing since they may be used for data-driven consumer loyalty programs, service customisation, and promotion. Nevertheless, network infrastructure, digital literacy, and microbusiness costs continue to be barriers to this technology's adoption. Additionally, the investigation revealed differences in adoption according to industry, company size, and geographic area, necessitating inclusive and flexible policies. In order to improve digital literacy, build payment infrastructure, and create evidence-based policies to increase MSME involvement in the country's digital economy ecosystem, this study suggests collaboration between the government, financial institutions, and fintech companies.